2023
DOI: 10.3390/jcm12072474
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Opioid Imbalance as a Potential Factor Involved in the Pathogenesis of Chronic Kidney Disease-Associated Pruritus in Dialysis Patients

Abstract: Chronic pruritus is one of the most common symptoms of dermatological diseases. It may occur in the course of other disorders, such as kidney disease. Chronic kidney disease-associated pruritus (CKD-aP) most often affects people with end-stage renal disease. The etiology of this condition is still not fully understood, but researchers are currently focusing on a thorough analysis of the association between disturbed opioid balance and increased neuronal signaling leading to pruritus. The aim of this study is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…In contrast, leu-enkephalin concentration was significantly lower in patients with ESKD as compared with healthy control and was not affected by dialysis [22]. Similar results were obtained by Wala-Zieli ńska et al [23] who investigated the correlation of CKD-associated pruritus with concentrations of endogenous opioids. In this study, the concentration of met-enkephalin was higher in the group of dialysis patients with pruritus compared to the healthy control group, whereas no significant differences in leu-enkephalin serum levels were found between the study groups.…”
Section: Penk a And Hemodialysissupporting
confidence: 70%
See 1 more Smart Citation
“…In contrast, leu-enkephalin concentration was significantly lower in patients with ESKD as compared with healthy control and was not affected by dialysis [22]. Similar results were obtained by Wala-Zieli ńska et al [23] who investigated the correlation of CKD-associated pruritus with concentrations of endogenous opioids. In this study, the concentration of met-enkephalin was higher in the group of dialysis patients with pruritus compared to the healthy control group, whereas no significant differences in leu-enkephalin serum levels were found between the study groups.…”
Section: Penk a And Hemodialysissupporting
confidence: 70%
“…In a study that evaluated the utility of PENK A in stable ambulatory patients with HF, higher levels of PENK A were associated with lower eGFR and decreased EF [17]. In another cohort of patients with new onset or worsening heart failure, higher PENK A levels were found in patients with more severe HF (reflected by a higher NYHA score and higher natriuretic peptides) and with poorer kidney function (higher creatine and urea levels, lower eGFR) [23]. Importantly, in all of the studies investigating PENK A in patients with HF, PENK A levels were strongly associated with eGFR [17,18,25].…”
Section: Penk a In Patients With Heart Failurementioning
confidence: 99%
“…Researchers from our center focused on recent studies on serum levels of interleukin (IL)-31 and neurotrophin-4 in patients with CKD-aP requiring HD, proving that their concentrations are significantly higher in this particular group [ 12 , 13 ]. Moreover, a recent study demonstrated that disturbance in the balance between the concentrations of the individual components of the opioid system might lead to the development of pruritus or modulate it in patients requiring HD [ 14 ].…”
Section: Introductionmentioning
confidence: 99%